Resepsi Pembaca terkait Berita Demo 4/11 di Kompas.com - Novita Ika Purnamasari (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
This study aims to determine the meaning of news readers in online media related to 4/11 demonstration news in Kompas.com. The central premise of this research is about freedom of expression and religious tolerance in Indonesia. This study uses four informants from students and reception analysis as the method with Carolyn Michelle as the model of analysis. Research on news readers in online media is so essential in media audience review in the new media era, where audiences have high media habit and also high access to information. Also, there is a change in the access pattern of news that is influenced by the media habit made by the reader. The issue raised in this study is interesting because it involves political and religious context. The result shows that from the 4/11 demonstration news, freedom of opinion and in Indonesia experienced a shift in spiritual meaning and tolerance to be polemic because religion should be unifying amidst a plural Indonesian society is used to spark conflict. This study also shows that personal experience, knowledge and media habits followed by good media literacy affect the meaning.